A Precise Dispenser Design for Canine Cognition Research. Issue 1 (2nd February 2022) - Arce, Walker; Stevens, Jeffrey R.
Some forms of canine cognition research require a dispenser that can accurately dispense precise quantities of treats. When using off-the-shelf or retrofitted dispensers, there is no guarantee that a precise number of treats will be dispensed. Often, they will over-dispense treats, which may not be acceptable for some tasks. Here we describe a 3D-printed precise treat dispenser with a 59-treat capacity driven by a stepper motor drive and controlled by an integrated Raspberry Pi. The dispenser can be built for less than 200 USD and is fully 3D printable. While off-the-shelf dispensers can result in an error rate of 20–30%, the precision dispenser produces a 4% error rate. This lower error rate and the integrated Raspberry Pi allows for new possibilities for using treat dispensers across a range of canine research questions. Metadata Overview: Main design files: https://github.com/unl-cchil/canine_precise_dispenser Target group: Scientists in canine cognition. Skills required: desktop 3d printing – easy; through-hole soldering – easy; hand tool use – easy Replication: No builds known to the authors so far. See section "Build Details" for more detail .